2019
DOI: 10.17221/72/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DualEM-II sensor for soil moisture content estimation in the potato fields of Atlantic Canada

Abstract: The conventional gravimetric methods of estimating soil moisture content (θ) are laborious, time-consuming, and destructive to agricultural fields. We evaluated the performance of DualEM-II sensor in non-destructive way of θ prediction and for predicting θ variations within potato fields in Atlantic Canada. Values of θ were measured from four potato fields in New Brunswick and Prince Edward Island using a pre-calibrated (R<sup>2</sup> = 0.98) time domain reflectometry (TDR) from root zone of potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…The tuber yield obtained from Fields 1 and 2 was higher than the country average vales of tuber yield of nations from Europe and America that adopt the best nutrient management practices, as tabulated by Koch et al [57]. The values of SOM and pH reported in Tables 1, 3 and 4 of this study are in the neighborhood of the values reported by Farooque et al [31], measured in two potato fields of New Brunswick and two in PEI. Moreover, the values of P and K reported by Zare et al [56] that resulted in enhanced tuber yield in potato fields of PEI and New Brunswick are in the range of the values of P and K of excellent and medium zones, or high yield producing portions of Fields 1 and 2 of the current study.…”
Section: Cluster Analysis and Management Zonescontrasting
confidence: 53%
See 2 more Smart Citations
“…The tuber yield obtained from Fields 1 and 2 was higher than the country average vales of tuber yield of nations from Europe and America that adopt the best nutrient management practices, as tabulated by Koch et al [57]. The values of SOM and pH reported in Tables 1, 3 and 4 of this study are in the neighborhood of the values reported by Farooque et al [31], measured in two potato fields of New Brunswick and two in PEI. Moreover, the values of P and K reported by Zare et al [56] that resulted in enhanced tuber yield in potato fields of PEI and New Brunswick are in the range of the values of P and K of excellent and medium zones, or high yield producing portions of Fields 1 and 2 of the current study.…”
Section: Cluster Analysis and Management Zonescontrasting
confidence: 53%
“…Loss of SOM leads to poor water infiltration through soil and slow drainage, increase in saturated soil conditions, and electrical conductivity and resultantly soil's ability to buffer electrical conductivity [50]. Farooque et al [31] evaluated spatial variability of HCP and θ measured in two potato fields of New Brunswick and two in PEI, different from the fields used in this study, and reported average values of HCP and θ in the range of this study.…”
Section: Variability In Crop and Soil Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…Australian Journal of Soil Research, 25, 21-27. Zare, M., Farooque, A. A., Abbas, F., Zaman, Q., & Bos, M. (2019).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Given the importance of this crop to the economy of Atlantic Canada in particular, and globally, timely forecasting of tuber yield would provide producers with valuable information for making informed management decisions during the growing season (Al-Gaadi et al, 2016). Like other crops, potato tuber yield is affected by soil physical, hydrological and chemical properties (Mair et al, 2007;Zare, Farooque, Abbas, Zaman, & Bos, 2019) for which ECa can be used as an indirect indicator (Farooque et al, 2019). Although several studies have investigated the application of ECa in precision farming of various crops, very limited research has been conducted to assess the prediction accuracy of ECa readings produced by the DualEM-2 instrument to estimate potato tuber yield.…”
Section: Introductionmentioning
confidence: 99%